Testing and modeling tensile stress-strain curve for prestressing wires in railroad ties - Chen, Yu-Szu (Kansas State University, 2016)
Prestressed concrete is commonly used for bridges, pavement and railroad ties because of economic advantages in cost, sustainability service life, and environmental friendliness. In general concrete design standard, the ultimate moment strength in flexure design is computed by finding the equilibrium of the internal force in the section (the compressive force in concrete and tension force in the steel and reinforcement). To predict tension force in steel one generally applies the 7-wire low-relaxation prestressing strand equation from the PCI manual even though the design employed prestressing wires instead of strand. The other method is to use equations from the ACI Code which is over conservative. Considering both approaches are lack accuracy, this research will provide an accurate estimation of the stress in prestressing wires through an experimental program and analytical modeling. The real stress-strain curves are collected through experimental testing in 13 types of prestressing wire. Experimental results are then used for modeling existing equations. As a result a more precise estimation is achieved. Additionally, this research simplifies the procedure for utilizing the equations which offers convenience in practical application.
Keywords: railroad tie; bridges; analytical modelingPrestressing wire